Case Report: A Pediatric Case of Lipoprotein Glomerulopathy in China and Literature Review - Song, Yue; Yang, Changqiang; Liu, Lan; Wang, Hua (Frontiers in Pediatrics, 2021)
Abstract Background: Lipoprotein glomerulopathy is a rare kidney disease characterized by lipoprotein thrombi in the glomerulus. Here, we report a case of lipoprotein glomerulopathy in a Chinese pediatric patient. Furthermore, we summarized the clinical features and genetic characteristics of lipoprotein glomerulopathy in China. Case Presentation: An 11-year-old Chinese girl presented with nephrotic syndrome with anemia (98 g/L). After excluding secondary causes, primary nephrotic syndrome was considered. Treatment with prednisone (60 mg/day) did not improve her condition. Renal biopsy showed marked dilation of the capillary lumen with lipoprotein thrombi and positive oil red O staining. Genetic testing revealed the genetic variant c.127C>T (p.R43C), known as the Kyoto mutation of the APOE gene. These findings are consistent with the diagnosis of lipoprotein glomerulopathy. Prednisone was gradually tapered and captopril was initiated. A two-year follow-up revealed elevated urine protein and serum creatinine levels. We also reviewed 17 pediatric and 156 adult cases of lipoprotein glomerulopathy reported in China from the year of creation to 2021. The most common clinical features were edema, hematuria, hypertriglyceridemia, and increased serum apoE levels. Extra-renal manifestations included anemia, splenomegaly, and cardiac lipoprotein deposition. Conclusion: APOE Kyoto is the most common mutation in patients with lipoprotein glomerulopathy. In China, homozygosity for E3 (E3/3) is the most common isoform.